Pengenalan Biota Akuatik Aliran Sungai Senggarang dengan E-Katalog Melalui Pembelajaran Tatap Muka Sesuai Protokol Kesehatan Covid-19 - Wahyu Muzammil; Tri Apriadi; Winny Retna Melani; Andi Zulfikar; Deni Sabriyati (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2021)
Small islands have short rivers characteristics, small catchment areas so that the ability to absorb rainwater into the ground is also reduced, such as the flow of rivers in Senggarang, Tanjungpinang City. Research related to aquatic biodiversity in Senggarang river flow has been carried out, the availability of information about the freshwater ecosystems that exist there is an interesting thing to inform the high school students as a generation of learners who lived near Senggarang river. The introduction of the aquatic biota of Senggarang river is expected to increase the sense of care, willingness, and insight in saving the resources of aquatic biota of Senggarang river flow will be sustainable. An introduction to the aquatic biota of the Senggarang river flow with the participants of class XI State High School 6 Tanjungpinang. The activity was carried out in three stages, namely a pre-test of knowledge about aquatic biota of the Senggarang river flow through quizizz media, education of any aquatic biota in the Senggarang river through e-catalog media containing pictures and descriptions of biota identification, and post-test with the same questions as the pre-test through the quizizz media to measure the extent to which students recognition, knowledge, and understanding have increased regarding the aquatic biota of the Senggarang river. The level of recognition, knowledge, and understanding of students increased from a very low–moderate range to a moderate–high range. Teaching media in the form of an e-catalog is very effective in introducing aquatic biota from the Senggarang river flow, according to the target stakeholders who are still in high school education.